Social workers and recovery from stress. (September 2021) - van Dam, Arjan; Noordzij, Gera; Born, Marise
Summary: Recovery from stress is essential for employees' well-being, even more so in jobs where high stress is inevitable. The purpose of this study was to examine the influence of achievement goal orientation on recovery from stress (i.e. need for recovery and vigour) over several years. We followed a sample of social workers in the Netherlands (N = 238) across four years, with three measurement points (T1–T3). Data were analysed with latent growth curve modelling. Findings: Results showed that need for recovery and vigour were fairly stable over time and therefore we could not examine the effects of achievement goal orientation on change in vigour and need for recovery over time. However, level of mastery goal orientation (mastery-approach and mastery-avoidance goal orientation) at T1 was positively related to the initial level of vigour at T1, even after controlling for job autonomy and workload. Our results indicate that mastery goal orientation is relevant for employees to feel energetic and vital in a job with high stress. Practical implications: Our results showed that organizations can prevent depletion among social workers by ensuring an acceptable workload, while vigour can be enhanced by selecting employees with high mastery goal orientation. Organizations can also contribute to the vitality of social workers by stimulating and fostering mastery goal orientation.